High Efficiency Cleaning Processes for Direct Wafer Bonding. (24th August 2016) - Dussault, Donald; Rothballer, Jan; Kurz, Florian; Reichardt, Make; Dragoi, Viorel
Abstract : Substrate cleaning is a very important process step in direct wafer bonding. Current work describes development, testing and verification of a single wafer megasonic cleaning method utilizing a transducer design that meets the extreme particle neutrality, Particle Removal Efficiency (PRE), and repeatability requirements of production scale wafer bonding and other applications requiring extremely low particle levels. The results were obtained using 300 mm diameter Si wafer which were processed as received, without any wet bench cleaning process. These experiments simulated real case production scenario in which the particle counts on incoming wafers are typically 0.1 LPD/cm 2 and lower.